Reclaiming Justice: International Legal Dimensions of Land Reclamation on Human Rights, Sovereignty, and Environmental Equity - Riska Kartini; Dedy Ardian Prasetyo; Supot Rattanapun (Journal Evidence Of Law, 2025)
Land reclamation has emerged as a global practice that extends far beyond technical infrastructure development, positioning itself at the crossroads of human rights, state sovereignty, and environmental justice. Despite the proliferation of studies addressing its ecological and economic impacts, a notable gap remains in scholarship that systematically integrates these three international legal dimensions. This study aims to address that gap by situating reclamation within the framework of international law, critically examining its normative implications. Employing a normative, juridical, and qualitative approach, the research relies on primary legal sources, including UNCLOS 1982, ICCPR 1966, ICESCR 1966, and key environmental declarations, complemented by case law from the ICJ and PCA. Secondary sources were collected through a comprehensive literature review across international databases and reports from global institutions. Data analysis was conducted through a hermeneutic interpretation of legal texts and a comparative examination of state practice. Findings reveal that reclamation often undermines the right to livelihood and a healthy environment, challenges the integrity of sovereignty when used to justify territorial expansion, and exacerbates ecological injustice by privileging elite interests over vulnerable communities. These results underscore the interdependence of rights, sovereignty, and environmental sustainability, suggesting the need for integrative normative frameworks. The study contributes to academic discourse by bridging fragmented literatures while offering practical guidance for policymakers. It highlights the urgency of embedding human rights impact assessments within environmental evaluations and strengthening regional consultative mechanisms to align reclamation practices with global legal norms